Primary Hodgkin’s lymphoma with chest wall ulceration and hypereosinophilia: a rare presentation and diagnostic dilemma - Wan Ali, Wan Ahmad Syahril Rozli; Tumian, Nur Rafeah (2018)
Hodgkin’s lymphoma (HL) with cutaneous manifestation is a rare condition which usually occurred late in the course of the disease. Due to its rare presentation, misdiagnoses are common. We report a 26-year-old Chinese gentleman who presented with painless and large anterior chest wall ulceration. Computed tomography scan showed sternal mass and erosion, with skin and anterior mediastinal extension. The second histopathologic examination (with immunohistochemistry) of the skin biopsy showed HL with mixed cellularity pattern. However, there was a marked dominance of eosinophils in both the peripheral blood and the tissue samples. This was a very unusual presentation of extranodal HL with ulceration and pronounced hypereosinophilia. The diagnosis was only made after the second biopsy because of the rare occurrence.